Notes for Teacher's Education in the Ethical-Political Perspective and Philosophy of Práxis - Roberto Francisco de Carvalho; Deise Mancebo (Universidade Federal de Santa Catarina, 2019)
This article discusses the teacher's education from the ethical-political and the philosophy of praxis perspectives. It addresses the conception of Gramscian education articulated to the concepts of society, man, knowledge, politics and presents some developments that this theoretical orientation can bring to the teacher's education. In order to achieve this goal, a bibliographical research was carried out, which allowed for reflections on the understanding of expanded   State, ideology, philosophy of praxis, education, school and notes about the teacher's education in the logic of the active and creative unitary school. In the end, it analyzes the Gramscian conception of higher education and its fundamental function of creation and cultural organization in society, giving unity to the process of intellectuals' training of diverse levels, including teachers.